Self Awareness Students Of SMPN 4 Sei Rampah About Early Detection Of Breast Cancer In 2020 - Lilis Novitarum; Vina Sigalingging; Bennaria Panjaitan (Sean Institute, 2023)
The incidence of breast cancer in Indonesia is still very high, most are detected at an advanced stage, therefore it is very important to do breast self-examination (BSE). To do BSE requires self-awareness, especially from a very young age considering The risk factor for breast cancer is early menstruation. The purpose of this study is to identify Self-Awareness of SMPN 4 Sei Rampah students regarding Early Detection of Breast Cancer.This type of research is descriptive analytic with cross sectional design. The population in the study were all students of SMPN 4 Sei Rampah with a total sample of 71 people. The sampling technique uses simple random sampling. Result showed good Self-Awareness as many as 62 people (87.3%). This shows that the Self-Awareness of SMPN 4 Sei Rampah students regarding Early Detection of Breast Cancer in 2020 is good. It is hoped that young women will increase self-awareness about early detection of breast cancer in order to reduce the incidence of breast cancer.